2018
DOI: 10.1093/cid/ciy045
|View full text |Cite
|
Sign up to set email alerts
|

Persistent High Burden of Advanced HIV Disease Among Patients Seeking Care in South Africa’s National HIV Program: Data From a Nationwide Laboratory Cohort

Abstract: BackgroundThe South African national HIV program has increased antiretroviral therapy (ART) coverage over the last decade, supported by policy changes allowing for earlier ART initiation. However, many patients still enter care with advanced (<200 cells/μL) and very advanced (<100 cells/μL) HIV disease. We assessed disease progression at entry to care using nationwide laboratory data.MethodsWe constructed a national HIV cohort using laboratory records containing HIV RNA loads and CD4 counts from 2004 to 2016 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
123
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(138 citation statements)
references
References 21 publications
13
123
2
Order By: Relevance
“…In South Africa, 56.7% of patients entering care in 2017 with very advanced HIV disease were treatment experienced (20). The prevalence of advanced HIV disease was lower in the current study than reported in the literature [18][19][20][21]; however, this could have been due to the variable uses of CD4 testing across included countries within the current study. During the study period, CD4 was still used to monitor treatment as access to viral load testing was significantly below coverage rates in South Africa [5].…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…In South Africa, 56.7% of patients entering care in 2017 with very advanced HIV disease were treatment experienced (20). The prevalence of advanced HIV disease was lower in the current study than reported in the literature [18][19][20][21]; however, this could have been due to the variable uses of CD4 testing across included countries within the current study. During the study period, CD4 was still used to monitor treatment as access to viral load testing was significantly below coverage rates in South Africa [5].…”
Section: Resultscontrasting
confidence: 75%
“…Several recent studies have highlighted the continued significant burden of advanced HIV disease. In 2016 in South Africa, for example, nearly a third (32.9%) of over 650,000 HIV-positive patients had advanced HIV disease at the time of their first CD4 count prior to ART initiation [18]. Further, reviewing CD4 data in nearly one million patients attending health care facilities within the IeDEA and COHERE cohorts across 55 countries found that not only has the proportion of patients entering care remained high across settings (31% in low-income countries, 40% in low-and middle-income countries, 29% in high-income countries), but these rates have plateaued over the past few years [19].…”
Section: Resultsmentioning
confidence: 99%
“…While the proportion of PLHIV starting ART with advanced disease has declined in recent years, they remain a significant portion of all patients enrolling in care and starting treatment in reports from across sub Saharan Africa . A retrospective analysis of almost 700,00 adults across 10 countries also showed a decline in advanced disease status at ART initiation but in several countries, up to 20% of patients continue to start treatment with CD4 < 100 copies/mm 3 .…”
Section: Resultsmentioning
confidence: 99%
“…[3] Approximately one-third of patients entering HIV care in the SA public sector in 2016 had advanced HIV disease (defined as a CD4+ T-lymphocyte count <200 cells/µL), and 17% had a CD4+ count <100 cells/µL. [4] In 2011, the World Health Organization (WHO) recommended that countries consider integrating cryptococcal antigen (CrAg) screening into HIV programmes to detect cryptococcal disease at an earlier point in its trajectory, followed by pre-emptive antifungal treatment to reduce AIDS deaths. [5] The CrAg screen-and-treat intervention therefore aligns with the Joint United Nations Programme on HIV/AIDS (UNAIDS) over-arching goal to reduce global AIDS deaths to >500 000 by 2020, and has been included in a new WHO-recommended package of care for managing advanced HIV disease.…”
Section: Editorialmentioning
confidence: 99%